Patterns of lipids and estrogen in women visiting the fertility clinic of Komfo Anokye Teaching Hospital, Kumasi, Ghana - Antwi, Joseph Sarfo; Addo, Kweku Bedu; Krokoe, Frank Ankobea (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility, which affects one in six couples, is a major clinical and social problem. Pelvic inflammatory diseases (PID) and sexually transmitted infections are but two of the several causes of infertility. The influence of lipid patterns and estrogen on infertility in the setting is however not fully explained. Therefore, the study sought to establish the Patterns of lipids and estrogen among infertile women visiting Komfo Anokye Teaching Hospital, Kumasi. Methods: The design was both retrospective and introspective study. Sampling technique was convenience and random probability sampling using a list of women with fertility challenges who attended KATH for infertility treatment. Univariable associations were tested using chi-square and a logistic regression was performed to assess the influence of lipids and estrogen on infertility. Associations were considered significant at p values of <0.05. Results: BMI was significantly associated with fertility in this study. The percentage of respondents who were overweight and obese was significantly higher among the women who were non-fertile as compared to those who were in the control group ((81.4% vrs 18.6% and 84% vrs 16% respectively). An increase in LDL cholesterol and total cholesterol were associated with increased likelihood of infertility among the subjects (OR, 95% CI=4.34, 2.18-8.65) and (OR, 95% CI=1.86, 1.03-3.35) respectively. A unit increase in BMI of the women is associated with 13% increase in the odds of being infertile, (OR, 95% CI=1.13, 1.01-1.65). A unit increase in estrogen level was also associated with 11% decrease in the odds of becoming infertile among the women studied (OR, 95% CI=0.89, 0.85-0.92). Conclusions: This study shows the influence of body mass index and high cholesterol levels on infertility. This finding will be useful in directing educational interventions aimed at promoting healthy lifestyles to reduce lipid levels and improve fertility among women.